Critical Thinking Ala Nabi Musa: Tafsir Surat Al-Kahfi Ayat 60–82 KH. Bahaudin Nursalim - A. M. Miftah Anshori; Nadia Sabilannaja (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2026)
This study aims to analyze the pedagogical and epistemological dimensions in the story of Prophet Moses and Khidr in QS. Al-Kahf verses 60–82 based on the interpretation of Bahauddin Nursalim. The primary focus is to examine the dialectic between sharia (normative law) and haqiqah (spiritual truth) and its implications for contemporary Islamic education. This research employs a qualitative approach with a library research design, utilizing content analysis of the Qur’an, classical and contemporary tafsir literature, and selected lectures of Gus Baha. Data were analyzed through reduction, display, and conclusion drawing using a descriptive-analytical method. The findings reveal that the narrative represents two epistemological models in Islam: normative rationality grounded in sharia and spiritual depth rooted in haqiqah. Prophet Moses’ critical responses reflect a value-based critical thinking model, while Khidr’s actions embody divine wisdom that transcends empirical reasoning. From a pedagogical perspective, the teacher-student relationship in this narrative highlights the importance of dialogical learning that integrates critical inquiry, patience, and respect for scholarly authority. This study implies that the story serves as a conceptual foundation for developing contemporary Islamic education, particularly in balancing rationality and spirituality.